Development of Microbiology Handout as Teaching Material to Improve Science Process Skills of Health Vocational Students - Pratama, Aris Yudha; Hastuti, Utami Sri; Setiowati, Frida Kunti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This research is a research and development of Microbiology Handout on the topic